2000
DOI: 10.1046/j.1439-0507.2000.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum concentration on Candida biofilm formation on acrylic surfaces

Abstract: The biofilm formation of the oral fungal pathogen Candida on denture acrylic strips coated with saliva, serum and, saliva-serum pellicle were examined in vitro using Candida albicans (four isolates), Candida glabrata (three isolates) and Candida tropicalis (three isolates). The degree of biofilm activity varied depending upon both the isolate and the pellicle. Significantly increased biofilm activity on the pellicle (particularly serum)-coated strips was observed with three isolates of C. albicans and another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
(4 reference statements)
0
50
0
Order By: Relevance
“…Since peptone is an ingredient of other media, like YPD, which do not immediately induce hypha formation and which facilitate the formation of a basal yeast cell polylayer during bio-film formation (3; Daniels and Soll, unpublished), it seems unlikely that the peptone in Spider medium causes the rapid induction of hyphae that results in the absence of a basal yeast cell polylayer. Finally, it has been demonstrated that coating silicone elastomer with bovine serum, a step used to prepare the elastomer for biofilm adhesion in Spider medium, does not inhibit the formation of a yeast cell polylayer (3,63). Therefore, we have tentatively concluded that it is the beef extract peptides in Spider medium that rapidly induce hypha formation and that result in the absence of a basal yeast cell polylayer.…”
Section: Discussionmentioning
confidence: 77%
“…Since peptone is an ingredient of other media, like YPD, which do not immediately induce hypha formation and which facilitate the formation of a basal yeast cell polylayer during bio-film formation (3; Daniels and Soll, unpublished), it seems unlikely that the peptone in Spider medium causes the rapid induction of hyphae that results in the absence of a basal yeast cell polylayer. Finally, it has been demonstrated that coating silicone elastomer with bovine serum, a step used to prepare the elastomer for biofilm adhesion in Spider medium, does not inhibit the formation of a yeast cell polylayer (3,63). Therefore, we have tentatively concluded that it is the beef extract peptides in Spider medium that rapidly induce hypha formation and that result in the absence of a basal yeast cell polylayer.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of serum or salivary pellicles, which are normally found in the oral environment and may provide binding sites for Candida (8,10), increased the initial adherence of C. dubliniensis cells to biomaterials and subsequent biofilm formation. Other investigators have previously shown that the presence of serum and salivary pellicles can potentiate C. albicans colonization of acrylic strips and denture lining materials (41)(42)(43)(44)(45)(46). SEM techniques revealed that similar to C. albicans biofilms (5, 23), mature C. dubliniensis biofilms consist of a mixture of yeast and filamentous forms embedded within exopolymeric material.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of substrate is not trivial, since prior studies indicated that chemical composition, degree of hydrophobicity, and the presence of sera, protein, or amino acids affect Candida binding to surfaces (11,17,22,33,49). Other studies have shown that SE (the material used in the current study) allows better biofilm formation than other substrates (20), and our own unpublished observations support this finding.…”
Section: Discussionmentioning
confidence: 99%